2023
DOI: 10.1002/cpp.2861
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and psychological correlates of the COVID‐19 Anxiety Syndrome Scale: A comprehensive systematic review and meta‐analysis

Abstract: Coronavirus disease‐19 (COVID‐19) has led to the demise of millions of people worldwide; additionally, it has resulted in a significant economic and mental health burden. Since the onset of the COVID‐19 pandemic, various measures have been constructed to evaluate pandemic‐related fear and anxiety. The COVID‐19 Anxiety Syndrome Scale (C‐19ASS) is a promising measure that assesses coping strategies (e.g., avoidance, checking, worrying and threat monitoring), termed ‘COVID‐19 Anxiety Syndrome’, in response to COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…The C-19ASS has demonstrated a consistent factor structure, measurement invariance across gender and validity and reliability across different languages and cultures (Akbari et al, 2023). It could serve as…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The C-19ASS has demonstrated a consistent factor structure, measurement invariance across gender and validity and reliability across different languages and cultures (Akbari et al, 2023). It could serve as…”
Section: Discussionmentioning
confidence: 99%
“…an anxiety measure in future potential viral pandemics, perhaps by utilizing a relevant pandemic associated keyword instead of 'coronavirus' (Akbari et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, people with specific hobbies were more likely to have positive emotions in extreme work environments, and immersing oneself in something one enjoys gave one relaxation and a release from negative emotions. It is worth noting that the environment is also capable of acting on personal attributes and influencing them in some way, 29 , 30 and this dynamic relationship between personal attributes and the environment also plays an important role in pharmacists’ mental health. The findings of the present study revealed that the environment and people surrounding hospital pharmacists were another important influence on psychological state.…”
Section: Discussionmentioning
confidence: 99%